2011
DOI: 10.1109/tit.2011.2111710
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Statistical Tests for Single-Source Detection Using Random Matrix Theory

Abstract: Abstract-This paper introduces a unified framework for the detection of a single source with a sensor array in the context where the noise variance and the channel between the source and the sensors are unknown at the receiver. The Generalized Maximum Likelihood Test is studied and yields the analysis of the ratio between the maximum eigenvalue of the sampled covariance matrix and its normalized trace. Using recent results from random matrix theory, a practical way to evaluate the threshold and the p-value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
218
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(223 citation statements)
references
References 49 publications
3
218
0
2
Order By: Relevance
“…For a detailed proof we refer the reader to [3]. Here we provide an intuitive explanation for this: In the joint limit p, n → ∞, p/n → c, we have that …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…For a detailed proof we refer the reader to [3]. Here we provide an intuitive explanation for this: In the joint limit p, n → ∞, p/n → c, we have that …”
Section: Introductionmentioning
confidence: 95%
“…Classical examples include testing for the presence of interactions in multi-way data [8] and testing for equality of the population covariance to a scaled identity matrix [11]. Some modern signal processing applications include testing for the presence of signals in cognitive radio as well as non-parametric signal detection in array processing [2,3]. Normalized Wishart matrices (e.g., with trace equal to one) are also a common model for random density matrices in quantum information channels, see for example [14,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [8] it is shown that, in the asymptotic regime N, K → ∞ with K/N fixed, the GLRT detection performance converges to that of RLRT. However, a natural question is: Simulated receiver operating characteristics (ROC) curves for detection methods with known and unknown noise variance.…”
Section: Detection Performance Of Rlrt and Glrtmentioning
confidence: 99%
“…These methods do not require any prior information on the primary signal or on the noise power. In [30,31] two hypothesis tests allowing to detect the presence of an unknown transmitter using several sensors are proposed and random matrix theory is used to provide the error associated with both tests.…”
Section: Introductionmentioning
confidence: 99%